The Role of Educators in Improving Children's Spiritual Intelligence through Role Playing Learning Methods - Diah Two Sa'ban (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
Every child is unique. Children have different bits of intelligence, some have mathematical intelligence, language intelligence, musical intelligence, spiritual intelligence, and others. This research examines spiritual intelligence and the teacher's role in enhancing it through the role-playing method. Spiritual intelligence is an understanding of someone to perform worship in life in accordance with the beliefs they hold. Someone who has spiritual intelligence will associate everything they do with the beliefs they hold. To increase this spiritual intelligence needed the role of educators who help students to improve it. One role of educators is as a mediator and facilitator. Educators should choose what method is suitable for students to improve their spiritual intelligence. One method that can be done is the role-playing method. Researchers examine whether this role-playing method can increase students' spiritual intelligence.Keywords: Spiritual Intelligence, Role-Playing Methods, Educator Roles